THE ACCELERATED METHOD FOR IDENTIFICATION OF PATHOGENIC CORYNEBACTERIUM - Gabrielyan, S. A. (Infekt͡s︡ii͡a︡ i immunitet, 2014)
The detection of cystinase activity is one of most important tests in the laboratory diagnosis of diphtheria, giving the opportunity to differentiate potential toxigenic species from other coryneform bacteria. The original recipe of Pizu media for detection of cystinase activity, proposed in 1939–1940, was modified several times (1982, 1989) for different reasons. In the last modification the Pizu media was prepared by using the AGV media as a nutritional base. We suggest a modification of Pizu media using Mueller-Hinton agar as nutritional basis. The Mueller-Hinton agar has a number of advantages: higher nutritional value, standardization, transparency and availability. A positive result is defined within 2–4 hours after inoculation of enough quantity of material (pure culture or C. diphtheriaе in association with other microorganisms) as a brown halo surrounding black colonies. The brown halo does not appear in the upper part of the media (0,5–1 cm). The modified media was checked with 21 strains of C. diphtheriaе (tox+), nine strains of coryneform bacteria, control strains NCTC 10648, NCTC 10356, NCTC 3984. The modified Pizu media is registered in the RA mental property agency as an invention (no. 1877 A2, 15.12.2006).